Suppressing the δ-phase and photoinstability through a hypophosphorous acid additive in carbon-based mixed-cation perovskite solar cells - Shukla, Sudhanshu (2022)
Despite a meteoric rise in the efficiency and promising scalability aspects, the operational stability of halide perovskites poses a serious concern for the commercialization of this technology. A paradigm shift from thermally unstable MA+ (methylammonium)-based perovskites to stable FA+ (formamidinium) and Cs+ (cesium)-based mixed halide perovskite variants is a step in this direction. However, phase stabilization of mixed-cation halide perovskites within a triple-layer scaffold remains a major challenge. In this work, we demonstrate two-step sequential fabrication of FA+- and Cs+-based halide perovskites with formulation Cs0.05FA0.95Pb(IBr)3 in a triple-mesoscopic scaffold with a carbon layer as the back electrode. A strong but reversible performance degradation is observed under light illumination. Addition of hypophosphorous acid (HPA) into the perovskite precursor solution improves the operational stability of the cells. A striking correlation between phase- and operational stability was observed. From structural analysis, it was found that HPA tends to suppress the formation of a hexagonal yellow phase and promotes trigonal black phase formation. Further optical analysis of the cells showed the improvement in the optoelectronic properties in terms of defects and carrier recombination in the perovskite formed by HPA addition supported by external quantum efficiency and photoluminescence measurements. A stable 12% power conversion efficiency was achieved by tuning the composition and optimizing the process conditions for Cs0.05FA0.95Pb(IBr)3-based triple-mesoscopic perovskite solar cells.